Integration of the GPR and radio-impedance techniques in studies of the Baikal rift zone - Yu. B. Bashkuev; V. B. Khaptanov; M. G. Dembelov (Геодинамика и тектонофизика)
Radiowave propagation techniqueshave been very rarely applied to investigate tectonic fault zones and geoelectric profilesof the Baikal rift zone. In our study, we used a combination ofground-penetrating radar (GPR) and radioimpedance techniquesin order to identify and investigatetectonic crustal fault zones in the study area. Using soundings in the super-long, long and ultra short radio wave ranges(from tens of KHz to few GHz), we detected the tectonic fault zones in the seismically active Baikal rift zone, specifically in the Tunka depression and the areas of Southern Baikal and Kotokel lakes.Faults and fault zones were identified from impedance variations and changes in the geoelectric profiles by analyzing the radio impedance profiles and soundings in the super-long and long radio wave ranges. The georadiolocation of fault structures in the ultra-short wave range made it possible to differentiate thepatterns of tectonic disturbances up to individual seismic dislocations in sedimentary and crystalline rocks and to determine the kinematics of movements in the fault zones. The techniques used in this study complement each other and ensure obtaining adequate quantitative descriptions of the study objects. By integrating varioustechniques of radio wave diagnostics, it is possible to obtain more detailed information on the structures of the tectonic fault zones. The results obtained in this study and the radioimpedance and GPR sounding and profiling techniques developed to investigate a heterogeneous underlying medium can be used in seismological and geological engineeringsurveys of the eastern and northern regions of Russia.